Cohort Analysis of the Association of Delirium Severity With Cerebrospinal Fluid Amyloid-Tau-Neurodegeneration Pathologies. Issue 3 (14th July 2021) - Parker, Margaret; White, Marissa; Casey, Cameron; Kunkel, David; Bo, Amber; Blennow, Kaj; Zetterberg, Henrik; Pearce, Robert A; Lennertz, Richard; Sanders, Robert D
Abstract: Delirium is associated with cognitive decline and subsequent dementia, and rises in plasma total tau (tTau) and neurofilament light (NfL), providing links to Amyloid-Tau-Neurodegeneration (ATN) pathophysiology. We investigated whether changes in delirium severity after surgery correlated with changes in cerebrospinal fluid (CSF) ATN biomarkers. Thirty-two thoracic vascular surgical patients were recruited into a prospective biomarker cohort study with assessment of delirium severity and incidence (NCT02926417). CSF ( n = 54) and plasma ( n = 118) samples were sent for biomarker analysis for tTau, phosphorylated tau-181 (pTau) (plasma n = 53), NfL, and amyloid-β 42/40 ratio (Ab42/40-ratio). The primary outcome was the correlation of preoperative to postoperative change in ATN biomarkers with the highest postoperative Delirium Rating Scale-98 score. CSF and plasma biomarkers all increased postoperatively (all p < .05, n = 13 paired preoperative–postoperative samples). Delirium severity was associated with peak changes in CSF tTau ( p = .007, r = .710) and pTau ( p = .01, r = .667) but not NfL ( p = .09, ρ = .491) or Ab42/40-ratio ( p = .18, ρ = .394). Sensitivity analysis with exclusion of participants with putative spinal cord ischemia shifted the NfL result to significance ( p < .001, ρ = .847). Our data show that changes in tau and biomarkers of neurodegeneration in the CSF are associated with delirium severity. These data should be considered hypothesis-generating and future studies should identify if these changes are robust to confounding.